The Impact of ESG (Environmental, Social, Governance) Disclosure on Company Value with Audit Quality as a Moderating Variable - Raflesiana, Widhea Putri; Usman, Berto; Santi, Fitri (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
The purpose of this study is to analyze the impact of Environmental, Social, and Governance (ESG) disclosure on company value and to demonstrate the role of audit quality in moderating this impact. This study applies a quantitative approach. The population in this study includes all companies in the financial sector listed on the Indonesia Stock Exchange, while the sample consists of financial companies that regularly publish annual reports and sustainability reports between 2021 and 2023. This study applies panel data regression analysis, which combines two types of data, namely time series and cross-section, and applies Random-Effect Model (REM) analysis. The findings of this study indicate that ESG disclosure has a positive effect on company value, but individually, environmental disclosure has no effect, social disclosure has a significant positive effect, and governance disclosure has no effect, and audit quality moderation has no effect on ESG disclosure on company value.